2019
DOI: 10.1126/sciadv.aau7887
|View full text |Cite
|
Sign up to set email alerts
|

Bach1 regulates self-renewal and impedes mesendodermal differentiation of human embryonic stem cells

Abstract: The transcription factor BTB and CNC homology 1 (Bach1) is expressed in the embryos of mice, but whether Bach1 regulates the self-renewal and early differentiation of human embryonic stem cells (hESCs) is unknown. We report that the deubiquitinase ubiquitin-specific processing protease 7 (Usp7) is a direct target of Bach1, that Bach1 interacts with Nanog, Sox2, and Oct4, and that Bach1 facilitates their deubiquitination and stabilization via the recruitment of Usp7, thereby maintaining stem cell identity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 45 publications
(59 reference statements)
4
60
0
Order By: Relevance
“…Furthermore, the increased CSC-like properties induced by CIH were repressed by Bach1 knockdown. Though the effects of Bach1 on maintaining CSC-like property were little reported, our observation is consistent with previous reports that Bach1 can regulate self-renewal and stabilize Nanog, SOX2, and Oct4 in human embryonic stem cells [ 36 ]. Additionally, our previous study found that Bach1 can promote lung CSC phenotype by inducing CD44 expression (have not been published).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the increased CSC-like properties induced by CIH were repressed by Bach1 knockdown. Though the effects of Bach1 on maintaining CSC-like property were little reported, our observation is consistent with previous reports that Bach1 can regulate self-renewal and stabilize Nanog, SOX2, and Oct4 in human embryonic stem cells [ 36 ]. Additionally, our previous study found that Bach1 can promote lung CSC phenotype by inducing CD44 expression (have not been published).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to Smad3, Smad2 protein was also increased in Bach1 -deficient, injured muscle. Since Bach1 directly represses the expression of Nodal gene which encodes one of the ligands for the Smad pathway in human embryonic stem cells [ 42 ], Bach1 may regulate Smad pathway at multiple steps. Consistent with the previous report that Smad2 and Smad3 inhibit MyoD and myogenin expression [ 39 ], the expression of the two myogenic transcription factors was reduced in C2C12 cells upon knockdown of Bach1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DUB recruitment to substrates via adapter proteins can also be utilized to stabilize transcription factors. This is exemplified by USP7, which has recently been shown to be targeted to stemness factors SOX2, NANOG, and OCT4 via BACH1 to counteract their degradative ubiquitylation, thus ensuring hESC self-renewal [ 110 ]. Taken together, various mechanisms control the dynamic localization of DUBs to enable spatial restriction of ubiquitin signaling during development.…”
Section: Regulatory Principles Impinging On Dubsmentioning
confidence: 99%
“…This was proposed to stabilize these proteins and promote their function in the context of the PRC1 complex to repress the expression of pluripotency genes, ensuring faithful lineage commitment. In addition, recent reports have shown that both, USP21 and USP7 counteract degradative ubiquitylation of NANOG to ensure self-renewal of ESCs [ 110 , 143 ]. This example showcases how several DUBs can target the same transcription factor and it will be interesting to further explore how such interplay regulates ESC maintenance (e.g., through targeting differently localized pools of NANOG).…”
Section: Mechanisms How Dubs Control Developmentmentioning
confidence: 99%